Synchronization of directed complex networks with uncertainty and time-delay - Yunlong Wu; Qian Zhao; Hui Li (International Journal of Distributed Sensor Networks)
A complex earthquake monitor network includes satellite in-orbit and ground observation and requires good synchronization in time. This article investigates synchronization of complex networks with uncertainty and time-delay. Directed graphs are used to represent the interaction topology. The uncertainty is assumed to be norm bounded. Based on Lyapunov theory, sufficient conditions are given to guarantee the synchronization of the complex networks in the presence of time-delay. Simulation results are provided to demonstrate the effectiveness of the obtained results.